INTEGRATION OF INQUIRY LABORATORY ACTIVITIES IN ARCHIMEDES’ LAW LEARNING - Arianto, Ivan Setia; Wiyanto, Wiyanto; Sujarwata, Sujarwata (Physics Communication, 2018)
This research is aimed to know which ability students can develop through inquiry laboratory activities in Archimedes? law learning and its application to cognitive learning result. This research used mixed method. The quantitative data which were pre-test, post-test, and students? worksheets were taken to know the cognitive learning outcomes of students. Qualitative data presented in this research were video assisted observations and interviews with students as learning process. Those data were used to analyze the ability in observing, questioning, hypothesizing, designing, experimenting, interpreting data, and concluding which students can develop through inquiry laboratory activities in Archimedes? law learning. The N-gain shows that the inquiry laboratory activities in Archimedes? law learning improves students cognitive learning outcomes in SMP Islam Al Azhar 29 Semarang, SMP N 18 Semarang, and SMP Islam Al Azhar 14 Semarang. The Students? ability in observing, questioning, hypothesizing, designing experiments, experimenting, interpreting data, and concluding can develop with inquiry laboratory activities in Archimedes? law learning.